1. 5x + 8y +7
2. -48 +15w
3. m = -14
4. no
2007-03-12 18:37:15
·
answer #1
·
answered by okkim100 1
·
0⤊
0⤋
1. This is pretty simple :) With this you would want to combine like terms. That means the x's y's and the single numbers together. . -4x+7+8y+9x First you would move the like terms around so they're close to eachother and make sure to bring the sign with them thats infront. So when you move it around it becomes -4x+9x+8y+7 and combine the like terms. so the only like term you see is the two Xs. So then it's 5x+8y+7. Simple :) hope it helps
2.Distribute is pretty easy too. Just take the -3 and multiply it with all the numbers on the inside of the parenthesis (-3x16 + -5w x -3) that results in -48+15w it becomes +15 because of two negatives multiply to an equal number.
3. with these problems you always try to get "like terms" on the same side 3m - 1 = 5m + 27 since theres 2 m's you should try to get them on the same side. First subtract 3m from both sides so it equals -1 = 2m + 27 then once again follow the rule of trying to get like terms on one side. so subtract 27 which now equals -28=2m. Divide both sides by 2. Now m = -14.
4. This is fairly easy :) when you see x in the x^2+2 plug in x= -3 becuase they stated x= -3 :). So it's -3^2 +2 which is 11+ x-7 which is -10. So then 11 times - 10 = -110 now you see that y= -4 and that doesn't match our answer of -110 so it's not true. if you made y = -110 then it would be true
2007-03-13 01:47:31
·
answer #2
·
answered by John Le 1
·
0⤊
0⤋
1. - 4x +7 + 8y + 9x
= - 4x + 9x + 8y + 7
= 5x + 8y + 7 ----- Answer
2. - 3 (16-5w)
= - 48 + 15w ----- Answer
3. 3m - 1 = 5m + 27
= 5m - 3m + 27 + 1
= 2m + 28
m = - 28 / 2
m = -14 ------ Answer
4. Substitute (x = - 3 and y = - 4) into (y = x^2 + 2 times x - 7).
- 4 = - 3^2 + 2 times ( -3 - 7 )
= 9 + 2 times ( -10 )
- 4 = - 110
Answer: No
2007-03-15 14:12:27
·
answer #3
·
answered by ? 1
·
0⤊
0⤋
To simplify #1, we have to add like terms. Like terms are ones that have the same varible in them.
So, -4x+7+8y+9x
We know that x is in both -4x and 9x, so we can combine them.
5x+7+8y is our answer.
To distribute in #2, all that we have to do is multiply each of the 2 things inside the parentheses by the number outside of the parentheses.
-3(16-5w)=(-3)(16)-(-3)(-5w)
-48-15w is our answer.
On #3, we have to simplify just like the first one. This time, there's an equal sign. We have to add things to each side to isolate m on one side.
3m-1=5m+27
So, subtract 3m from each side.
3m-3m-1=5m-3m+27
-1=2m+27
Now, subtract 27 from each side.
-1-27=2m-27
-28=2m
Now, divide each side by 2.
-28/2=2m/2
-14=m is our answer.
On number 4, we must plug the numbers for x and y into the equation to see if the answer matches up on both sides of the equal sign.
y=(x^2+2)(x-7)
x= -3
y= -4
Plug the values of x and y into our equation
-4=((-3)^2+2)((-3)-7)
-4=(9+2)(4)
-4=(11)(4)
-4=44 This is wrong. x= -3 and y=-4 does not make the equation true.
I hope that this helps.
2007-03-13 01:39:07
·
answer #4
·
answered by unhrdof 3
·
0⤊
0⤋
1. simplify -4x +7 + 8y + 9x
=-4x+9x+8y+7
=5x+8y+7
2. distribute -3(16-5w)
-3(16)+(-3)(-5w)
=-48+15w
3. 3m - 1 = 5m + 27
adding-5m+1 to both sides
-2m=28
dividing by -2
m=-14
4. does X= -3 and y = -4 make the equation true?
y= x^2 +2 times x -7
LHS=-4
RHS=[(-3)^2+2][-3-7]
=11(-10)
=-110
no it doesn't
2007-03-13 01:40:04
·
answer #5
·
answered by raj 7
·
0⤊
0⤋
1.y = -(5x+7)/8
i solve for y
2.-48 + 15w
3.m=-14
4.y=x^2+2(x-7)
no it doesn' t make it true.
when x= -3, y = -11
if anyone does reread this, use the order of operation to do which operation first. Since there is not ( ) in the equation we can assume that we first do the multiplication first. So we first time 2(x-7), don't force your ( ) within the function when it wasn't given.
2007-03-13 01:31:21
·
answer #6
·
answered by iknowu2jan 3
·
0⤊
0⤋
I think
1. 5x+8y+7
2.
3. m= -14
4. yes
2007-03-13 01:44:05
·
answer #7
·
answered by bunnyrabbitt 1
·
0⤊
0⤋
iknow missed # 1
should be 5x + 8y + 7 (the way you have it written)
2007-03-13 01:36:04
·
answer #8
·
answered by John S 6
·
0⤊
0⤋